EVALUATION OF THE FARMACARE POINT OF SALE (POS) SYSTEM ON THE NUMBER OF TRANSACTIONS, TRANSACTION VALUE, AND MONTHLY REVENUE OF A PRIVATE PHARMACY IN GIANYAR, BALI - I Made Krisnawan Putra; Titien Siwi Hartayu (RADJA PUBLIKA, 2026)
The use of information technology in pharmacy management, such as Point of Sale (POS) systems, is part of digital transformation. Desktop-based POS applications are considered less up to date with the current needs of modern pharmacies; therefore, to improve efficiency, the pharmacy replaced the desktop-based POS with the web-based Farmacare POS system. This study aimed to evaluate the effect of the Farmacare POS on the average number of transactions, the average transaction value, and monthly revenue in a private pharmacy in Gianyar, Bali. This research employed a quasi-experimental design using a one-group pretest–posttest approach. The data were obtained from pharmacy sales transaction reports for six months before and six months after the implementation of the Farmacare POS. Data analysis was conducted using the Shapiro–Wilk normality test, followed by the Paired Sample T-Test and the Wilcoxon Signed Rank Test with a significance level of 0.05. The results showed a significant increase in the average number of transactions (p = 0.028) and monthly revenue (p = 0.032) after the implementation of the Farmacare POS, while the average transaction value increased but was not statistically significant (p = 0.065). Descriptively, the average number of transactions increased by approximately 5%, the average transaction value increased by 10.6%, and monthly revenue increased by 14.5%. Therefore, it can be concluded that the Farmacare POS system is able to improve the average number of transactions and monthly revenue, and thus can be regarded as an effective managerial support tool.